DRIE 공정 변수에 따른 TSV 형성에 미치는 영향 - 이영철; Young Chul Lee; 정승부; Seung Boo Jung; 송준엽; Jun Yeob Song; 김광석; Kang Seok Kim; 안지혁; Jee Hyuk Ahn; 유중돈; Chong D. Yoo (대한금속·재료학회지, 48(11), 2010)
In the development of 3D package, through silicon via (TSV) formation technology by using deep reactive ion etching (DRIE) is one of the key processes. We performed the Bosch process, which consists of sequentially alternating the etch and passivation steps using SF6 with O2 and C4F8 plasma, respectively. We investigated the effect of changing variables on vias: the gas flow time, the ratio of O2 gas, source and bias power, and process time. Each parameter plays a critical role in obtaining a specified via profile. Analysis of via profiles shows that the gas flow time is the most critical process parameter. A high source power accelerated more etchant species fluorine ions toward the silicon wafer and improved their directionality. With O2 gas addition, there is an optimized condition to form the desired vertical interconnection. Overall, the etching rate decreased when the process time was longer.